Non-functional lingual thyroid presenting with severe obstructive sleep apnea. Issue 1 (1st January 2016) - Manzi, Brian; Ho, Henry
Abstract: Lingual thyroid occurs when the thyroid fails to descend embryologically. Case presentation of a 20-year old morbidly obese female with obstructive sleep apnea (OSA) and hypothyroidism diagnosed with a lingual thyroid measuring 4 × 4.5 × 3.4 cm, treated with long-term flap tracheotomy and transoral laser microsurgical excision. Lingual thyroids have the potential to result in acute airway compromise. Lingual thyroids can appear asymptomatic due to gradual airway adaptation but show airway narrowing on imaging studies. This patient's OSA and hypothyroidism symptoms improved significantly post removal of lingual thyroid. Spontaneous hypothyroidism and OSA should be investigated and managed for optimal outcomes.